(untitled) - Reichard, Kevin (New York, N.Y., 1995)
A comprehensive introduction explains and evaluates twelve essential UNIX and X Window packages, covering installation and configuring, the text editor, the graphical e-mail package, and the C compiler.
Keywords: UNIX (tệp máy tính),UNIX (Computer file)